Exploring the association between multidimensional social isolation and heterogeneous cognitive trajectories among older adults: evidence from China - Xie, Xinlong; Lyu, Yanxia; Wu, Fanfan; Zong, Anpeng; Zhuang, Zhiruo; Xu, Aijun (Frontiers in Public Health, 2024)
Objective: This study aims to elucidate the heterogeneous cognitive trajectories among older adults in China through a comprehensive, nationally representative longitudinal study. Furthermore, it seeks to investigate the impact of multidimensional social isolation on heterogeneous cognitive trajectories among older adults in China.Methods: Utilizing data from three successive waves of the Chinese Longitudinal Aging Social Survey (CLASS) spanning 2016 to 2020, this investigation quantified baseline social isolation across three dimensions-family isolation, friend isolation, and subjective isolation-alongside cognitive function scores of older adults, measured across all three waves. Through latent class growth models, heterogeneous cognitive trajectories were delineated. The influence of family isolation, friend isolation, and subjective isolation on these cognitive trajectories was examined employing multinomial logistic regression analysis.The study included 6,378 participants aged 60 and above, revealing three primary cognitive trajectories: High baseline stable group (68.8%), High baseline but declining group (21.7%), and Low baseline deteriorating group (9.5%). Adjusting for variables such as personal physical characteristics, social networks, living and working conditions, and the surrounding policy environment, the findings indicated that family isolation did not significantly affect cognitive function's high-level decline or low-level deterioration. Conversely, friend isolation markedly increased the risk of high-level cognitive decline (OR=1.289) and low-level cognitive deterioration (OR=1.592). Similarly, subjective isolation significantly heightened the risk for both high-level decline (OR=1.254) and low-level deterioration (OR=1.29) in cognitive function.Mitigating friend and subjective isolation among older adults appears to be a more effective strategy in preventing or delaying cognitive decline, potentially reducing the strain on healthcare and social welfare systems.